Limpeza manual x limpeza automatizada: uma análise de carga microbiana de instrumentais cirúrgicos após o uso clínico em cirurgias do aparelho digestivo - Síntia de Souza Evangelista (2014)
Several health products (HP), among them the most surgical instruments, are designed in order to allow its reuse. The presence of microbial contamination on HP after its processing can limit the reuse of these instruments, because of the risk of cross-transmission of microorganisms, favoring the occurrence of Health Care-Associated Infections. The aim was to evaluate the microbial load present in surgical instruments used in the digestive tract surgeries after its clinical use and manual and automated cleaning. This was an experimental study carried out in the Laboratory of Oral Microbiology and Anaerobes. The sample was composed of 125 instruments from 25 gastrointestinal surgeries, potentially contaminated and contaminated, undergone two cleaning processes, manual and automated. The instruments were immersed in sterile plastic bags containing sterile distilled water and exposed to sonication in ultrasonic washer, followed by stirring. The samples were divided into five equal parts and filtrated on Millipore® membrane of 0.45m. The membranes were then deposited in specific culture substance for the assessment of microbial load and isolation of microbial groups of epidemiologic relevance. The identification of micro-organisms was performed on the system Vitek II Biomeriéux, with specific cards for each group of microorganisms. The average microbial load in the different stages was 93.1CFU/100ml after use, 41CFU/100ml and 8.24CFU/100ml in the two sequential steps of manual cleaning and 75CFU/100 and 16.1CFU/100ml in instrumental that went to automated cleaning. The reduction of microbial load between the sequential cleaning steps was not significant for instrumental undergoing the cleaning in ultrasonic washer. The microbial load after use was influenced by the potential for contamination of surgery. After the clinical use, 64% of the instruments showed microbial load higher than 101 and 102CFU/100ml. After the first stage of the manual method, 44% remained in this range, while this figure was 52% in those undergoing automated cleaning. At the end of the last stage of cleaning, it was not recovered microbial load in most instruments. However, approximately 10% had load greater than 10 and 100CFU/100ml. Negative Staphylococcus coagulase was among the micro-organisms commonly isolated in all stages evaluated. In addition, the main insulations by step were Escherichia coli after use, Pseudomonas spp. and Stenotrophomonas maltophilia after the first step of manual and automated cleaning, in the last Acinetobacter baumannii complexx also stood out. Manual cleaning with immersion in enzymatic detergent and brushing, in this study, demonstrated to be more effective when compared to that performed in ultrasonic washer, with a significant reduction of microbial load. However, the use of thermal disinfection at a subsequent stage was able to significantly reduce such instruments contamination in both methods.